The Influence of Madrasah Quality and Brand Image Through Electronic Word of Mouth (E-Wom) on the Decision to Enroll at MI PKP DKI Jakarta - Dorthi Agiviola (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Customer loyalty plays a vital role in restaurant businesses in maintaining both short-term and long-term relationships, ultimately driving profit growth and business sustainability. This study aims to analyze several factors influencing customer loyalty, including service quality, price, and customer satisfaction, using a quantitative research method. The research was conducted from October to December 2024 at six Padang restaurants located in Malinau Regency. The sample consists of 280 respondents aged 17 years and older, who have visited and made purchases at least twice. Data was collected through questionnaires using a Likert scale measurement (ranging from 1 to 5) and analyzed using Structural Equation Modeling (SEM) with Smart PLS 4.0 software. The study results indicate that service quality, price, and customer satisfaction have a positive and significant direct effect on customer loyalty. Additionally, the indirect effect (mediation) shows that service quality and price also have a positive and significant impact on customer loyalty through customer satisfaction. Despite these findings, Padang restaurant owners should continue to improve service quality, implement effective pricing strategies, and consider other factors such as product quality, customer trust, and relationships to ensure sustained customer satisfaction and loyalty growth.